2004
DOI: 10.1002/ajpa.20034
|View full text |Cite
|
Sign up to set email alerts
|

The role of changing childhood diets in the prehistoric evolution of food production: An isotopic assessment

Abstract: Earlier weaning has often been suggested as a cause for population growth after the evolution of food production. However, evidence for weaning-time reduction is largely circumstantial. Collagen stable nitrogen- and carbon-isotope ratios from juvenile and adult burials from four sites in eastern North America were measured to estimate weaning onsets and durations before and after the appearance of intensive food production. Two preagricultural Late Archaic sites (Indian Knoll and Carlston Annis) are compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 54 publications
(90 reference statements)
5
62
0
2
Order By: Relevance
“…A similar difference has been found in modern mother-infant pairs (Fuller et al, 2004(Fuller et al, , 2006a and some archeological sites (Katzenberg et al, 1993;Richards et al, 2002;Fuller et al, 2003;Schurr and Powell, 2005). This is commonly called a ''trophic level effect'' despite the fact that the differences in d 13 C between breast milk and substitute foods have not been systematically measured.…”
Section: Stable Isotopes and Breastfeedingmentioning
confidence: 61%
See 1 more Smart Citation
“…A similar difference has been found in modern mother-infant pairs (Fuller et al, 2004(Fuller et al, , 2006a and some archeological sites (Katzenberg et al, 1993;Richards et al, 2002;Fuller et al, 2003;Schurr and Powell, 2005). This is commonly called a ''trophic level effect'' despite the fact that the differences in d 13 C between breast milk and substitute foods have not been systematically measured.…”
Section: Stable Isotopes and Breastfeedingmentioning
confidence: 61%
“…Nitrogen stable isotope ratios in skeletal material are widely used for the interpretation of weaning in the past (e.g., Katzenberg et al, 1993;Schurr. 1997;Wright and Schwarcz, 1999;Dupras et al, 2001;Mays et al, 2002;Fuller et al, 2003;Schurr and Powell, 2005;Clayton et al, 2006;Dupras and Tocheri, 2007;Jay et al, 2008;Pearson et al, 2010). There is also a slight trophic level effect associated with d…”
Section: Stable Isotopes and Breastfeedingmentioning
confidence: 91%
“…15 N values in several archaeological skeletal populations (e.g., Schurr and Powell, 2005;Choy et al, 2010;Waters-Rist et al, 2011;Beaumont et al, 2013a).…”
Section: Infant Feeding Practicementioning
confidence: 99%
“…All exclusively breastfed infants had a dual enrichment in carbon (%1%) and nitrogen (%2-3%) when compared to maternal values. In contrast, breast-and formula-fed subjects had reduced enrichments compared to exclusively breastfed subjects, and the exclusively formula-fed infant showed no increase in Since the pioneering discovery that the nitrogen stable isotope ratio ( 15 N/ 14 N) in body tissues can be used to detect the age of weaning (Fogel et al, 1989), there have been numerous applications of this technique to reconstruct breastfeeding and weaning patterns in archaeological populations (Katzenberg et al, 1993;Katzenberg and Pfeiffer, 1995;Schurr, 1997Schurr, , 1998Herring et al, 1998; Schwarcz, 1998, 1999;Dupras et al, 2001;Mays et al, 2002;Richards et al, 2002;Schurr and Powell, 2005). These studies of bone chemistry revealed extensive information about the duration of breastfeeding in different cultures and time periods, and give anthropologists a glimpse of societal views and health patterns that are largely invisible in the archaeological record (Katzenberg et al, 1996).…”
mentioning
confidence: 98%